2011
DOI: 10.1108/03090561111167423
|View full text |Cite
|
Sign up to set email alerts
|

Consumer resistance and anti‐consumption

Abstract: PurposeThis paper aims to study consumer resistance and anti‐consumption in the context of illegal downloading of cultural goods in France. This practice is socially constructed as deviant by marketplace actors' moral labeling. To that extent, deviant careers are adopted as an analytic framework to articulate these two concepts.Design/methodology/approachA comprehensive approach was used. The authors conducted 49 in‐depth interviews in 2009. The data collected were then analyzed to build the different steps of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In each stage, different expressions or “green materialities” (Fuentes, 2014; Horton, 2003) participate in the formation of the green identity of organic consumers: a more rational consumption, the reinforcement of ecological awareness, joining exchange network groups, engaging in activism for environmental causes, home food cultivation, vegetarianism, living in the countryside, the reduction of goods at home, autonomy and subsistence, vegetarianism and resistance to consumption. The latter is considered to be the most salient one and implies redefining the meaning of consumption by adopting alternative ways of consumption or anti-consumption practices (Garcia-Bardidia et al , 2011), and a voluntary simplicity lifestyle (Shaw and Moraes, 2009; Zamwel et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In each stage, different expressions or “green materialities” (Fuentes, 2014; Horton, 2003) participate in the formation of the green identity of organic consumers: a more rational consumption, the reinforcement of ecological awareness, joining exchange network groups, engaging in activism for environmental causes, home food cultivation, vegetarianism, living in the countryside, the reduction of goods at home, autonomy and subsistence, vegetarianism and resistance to consumption. The latter is considered to be the most salient one and implies redefining the meaning of consumption by adopting alternative ways of consumption or anti-consumption practices (Garcia-Bardidia et al , 2011), and a voluntary simplicity lifestyle (Shaw and Moraes, 2009; Zamwel et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-consumption can be described as resistance, distaste or being against consumption, and can be viewed as a reflection of a lifestyle (Amine and Gicquel 2011;Lee et al 2011;Zavestoski 2002) to achieve societal and personal goals (Garcia- Bardidia et al 2011), with consumers deciding not to consume a range of products or services. At an individual level, this reflects an individual's overall (non)consumption of specific products or services (Iyer and Muncy 2009) by not purchasing these products.…”
Section: Anti-consumptionmentioning
confidence: 99%
“…Anti-consumption-that is, the act of deliberately avoiding any form of consumption (Lee et al 2009b)-is suggested to be triggered by excessive unsustainable consumption and the shift in power from brands to consumers by referring to their ability to ignore and resist efforts from marketers (Denegri-Knott et al 2006;Pentina and Amos 2011). Anti-consumption can be generalised for the consumption of all products and services as well as for specific products or brands, such as gambling or casino brands (Garcia-Bardidia et al 2011). The importance of the negative aspects of branding are increasingly acknowledged, with researchers arguing it is as important to understand why consumers avoid a specific product or brand (Fournier et al 2012;Hogg and Banister 2001;Knittel et al 2016;Lee et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…This article focuses on resistant consumers who not only incorporate a set of negative attitudes, but also adapt their consumption behavior to their convictions by at least reducing the consumption of specifi c brands or products. Compared to the concept of anticonsumption, consumer resistance is thus deciphered as a more active form of consumer behavior (Garcia-Bardidia et al, 2011: 1790, Galvagno, 2011: 1699. However, the results can just as well be applied to skeptical or cynic consumers.…”
Section: The Emergence Of Consumer Resistancementioning
confidence: 99%